2003
DOI: 10.1023/a:1024068525763
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Codon 655 Polymorphism and Risk of Breast Cancer in African Americans and Whites

Abstract: The HER2 codon 655 polymorphism may be one of many low-penetrant genes that make a minor contribution to breast cancer, particularly in subgroups of women. Additional large studies, as well as data pooling, will be needed to estimate the contribution of such genes to breast cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 19 publications
7
71
1
1
Order By: Relevance
“…Additionally, it also raised a possibility that the risk associated with carrying the HER‐2 valine allele might predominantly affect pre‐ or peri‐menopausal breast cancer 78. Consistent with the above investigations, another study also suggested that that V/V or V/I genotype have a twofold increased risk compared with I/I genotype among women who were both younger than 45 years of age and reported a positive family history of breast cancer (OR = 2.3, 95% CI = 1–5.3) 79. However, some conflicting results emerged, revealing that HER‐2 I655V polymorphism may be a biomarker for breast cancer susceptibility among older women 80.…”
Section: The Her‐2 Mutations Associated With Breast Cancer Risksupporting
confidence: 63%
“…Additionally, it also raised a possibility that the risk associated with carrying the HER‐2 valine allele might predominantly affect pre‐ or peri‐menopausal breast cancer 78. Consistent with the above investigations, another study also suggested that that V/V or V/I genotype have a twofold increased risk compared with I/I genotype among women who were both younger than 45 years of age and reported a positive family history of breast cancer (OR = 2.3, 95% CI = 1–5.3) 79. However, some conflicting results emerged, revealing that HER‐2 I655V polymorphism may be a biomarker for breast cancer susceptibility among older women 80.…”
Section: The Her‐2 Mutations Associated With Breast Cancer Risksupporting
confidence: 63%
“…The relationship between the I655V genotype and HER-2 amplification has been suggested in previous studies (29,34), which showed that I655V is associated with HER-2 amplification and/or protein overexpression in breast cancer, although the number of cases was small and the results were not significant. If our result is not an incidental finding, it suggests that polymorphisms other than I655V may be associated with HER-2 protein expression and breast cancer progression.…”
Section: Discussionmentioning
confidence: 75%
“…In addition, no significant associations were found in subgroup analysis [e.g., within younger subjects (<45 years old), those who have a family history, or those with localized or in situ cancer; data not shown]. Previous studies (11,14,15,29) have shown that the association between I655V status and breast cancer risk became more significant in these subgroups.…”
Section: Resultsmentioning
confidence: 80%
“…Cases of invasive breast cancer were enrolled in two phases (phase 1: 1993-1996, phase 2: 1996-2001) with oversampling of African American and younger women (30). Controls were frequency matched to cases based on age and race (F5 years) using randomized recruitment (31).…”
Section: Methodsmentioning
confidence: 99%